Assessment of biodiversity in Chilean cattle using the distribution of major histocompatibility complex class II BoLA-DRB3 allele - Takeshima, S. N. (2015)
Bovine leukocyte antigens (BoLAs) are used extensively as markers for bovine disease and immunological traits. In this study, we estimated BoLA-DRB3 allele frequencies using 888 cattle from 10 groups, including seven cattle breeds and three crossbreeds: 99 Red Angus, 100 Black Angus, 81 Chilean Wagyu, 49 Hereford, 95 Hereford × Angus, 71 Hereford × Jersey, 20 Hereford × Overo Colorado, 113 Holstein, 136 Overo Colorado, and 124 Overo Negro cattle. Forty-six BoLA-DRB3 alleles were identified, and each group had between 12 and 29 different BoLA-DRB3 alleles. Overo Negro had the highest number of alleles (29); this breed is considered in Chile to be an ‘Old type’ European Holstein Friesian descendant. By contrast, we detected 21 alleles in Holstein cattle, which are considered to be a ‘Present type’ Holstein Friesian cattle. Chilean cattle groups and four Japanese breeds were compared by neighbor-joining trees and a principal component analysis (PCA). The phylogenetic tree showed that Red Angus and Black Angus cattle were in the same clade, crossbreeds were closely related to their parent breeds, and Holstein cattle from Chile were closely related to Holstein cattle in Japan. Overall, the tree provided a thorough description of breed history. It also showed that the Overo Negro breed was closely related to the Holstein breed, consistent with historical data indicating that Overo Negro is an ‘Old type’ Holstein Friesian cattle. This allelic information will be important for investigating the relationship between major histocompatibility complex (MHC) and disease.